Kajian Potensi Limbah Kotoran Manusia Sebagai Pembangkit Listrik Tenaga Biogas Di Kota Pontianak - Ardiansyah, Ardiansyah (ELKHA : Jurnal Teknik Elektro, 2017)
Abstract– Utilization of human waste as a source of energy can produce methane gas through anaerobic digestion process, where the resulting methane gas is converted into electrical energy. In this research both electrical energy capacity and economics feasibility of Biogas Power Plant development from the utilization of human waste in Pontianak City calculated.Based on the calculation and analysis of electrical energy capacity and economics feasibility, the potential of human waste in Pontianak City produces biogas of 3,091.94 m3/day, methane gas 2,164,36 m3/day, and electrical energy 24,157,88 kWh/day. The result of technical and economic analysis of energy conversion implementation using 250 kW microturbin produces electric power equal to 2,058,254,5 kW per year, pay back period 4 years 11 months, net present value 22,379.004.648 IDR, and internal rate of return of 18,681%, so the construction of Biogas Power Plant is feasible to be implemented. Keywords- anaerobic digestion, biogas, microturbine